Renbaan cave : stone tools, settlement and subsistence - Kaplan, Jonathan Michael (Department of Archaeology, 2018)
This project describes and interprets the results from the Renbaan Cave excavation and situates the site in the context of contemporary Later Stone Age studies in the southwestern Cape. It is designed to complement the research of professor John Parkington. It is argued that settlement and subsistance patterns at Renbaan Cave reflect similar patterns to those noted at other small cave/shelter sites in the research area. The availability of radiocarbon dates however, forces us to reconsider and question our previous perception of the distribution and occupation of late Holocene sites in the southwestern Cape. Important behavioural information has been located in the analysis of the stone artefact assemblage and new avenues of enquiry are suggested.